DYNAMICS OF FOREIGN INSTITUTIONAL INVESTMENTS AND EQUITY RETURNS IN INDIA - Singh, Rajdeep; Singh, Kanwaljeet; Kaur, Prabhjot (International Journal of Research -GRANTHAALAYAH, 2016)
India has become a focus point and an attractive hub for foreign investor’s post 199. This international flow of capital was facilitated by increased globalization and the growth of information technology which has blurred national borders. Thus FII flows in India have continuously grown in importance post 1991. This paper examines the trend of FII flow in India from 2001 and 2015 and also examines the relationship between FII and the two important barometers of the Indian stock market, i.e., S&P BSE Sensex and CNX Nifty. The impacts of FII on the proxies for stock market, i.e., Sensex and nifty have been studied by employing simple regression analysis using E-views.